Erysimum kamelinii, a new species from Middle Asia, and further additions to Polatschek's revision of the genus Erysimum (Cruciferae): part 1 - German, Dmitry (Annalen des Naturhistorischen Museums in Wien. B, Botanik und Zoologie, 2012)
Miscellaneous updates to the first part of the world-wide treatment of Erysimum (Cruciferae) by A. Polatschek are presented. Additional information on synonymy of several taxa is provided along with the distinguishing characters of some species which taxonomical status was questioned. Contribution also includes the description of a new species, E. kamelinii, and correction of distribution of several taxa.